Observable Laryngopharyngeal Lesions during the Upper Gastrointestinal Endoscopy - Park, Kyung Sik (Clinical endoscopy, 2013)
Regardless of outstanding developments in the endoscopic field, laryngopharyngeal lesions are generally considered as a field of otolaryngology, and thus it is thought that not a lot of gastrointestinal endoscopists commonly take interest in these lesions during the upper gastrointestinal endoscopic examinations. Therefore, here in this thesis, I reviewed the availability of upper gastrointestinal endoscopy in laryngopharyngeal area, normal structures of laryngopharynx, and the lesions that can be observed with the standard upper gastrointestinal endoscopic procedure.